Pengaruh Daya Tarik Wisata terhadap Minat Berkunjung Wisatawan di Objek Wisata Seribu Tangga Delleng Sindeka Kecamatan Salak Kabupaten Pakpak Bharat - Lastiarna Praninta Berutu; Ade Putera Arif Panjaitan; Tio RJ Nadeak; Masniar Hernawaty Sitorus; Maringan Sinambela (Journal of Creative Student Research, 2024)
The purpose of this study was to determine the positive and significant influence of tourist attractions on the interest of tourists to visit the Seribu Tangga Delleng Sindeka tourist attraction, Salak District, Pakpak Bharat Regency. The method used in this study is a quantitative research method. The population is the stakeholders of the Seribu Tangga Delleng Sindeka tourist attraction, Salak District, Pakpak Bharat Regency, including the Tourism and Culture Office of Pakpak Bharat Regency, village governments, tourist attraction managers, the community and tourists who are visiting and a sample of 67 people was determined using the accidental sampling method by Cochran. Data were collected with a closed questionnaire of 30 items. The results of the data analysis show that there is a positive and significant influence of tourist attractions on the interest of tourists visiting the Seribu Tangga Delleng Sindeka tourist attraction, Salak District, Pakpak Bharat Regency, as evidenced by the following data analysis: 1) a positive relationship test obtained a value of rxy = rxy = 0,521 > rtabel(=0,05,n=67) = 0,244, thus it is known that there is a positive relationship between variable X and variable Y. 2) A significant relationship test obtained a value thitung= 4,918 > ttabel(=0,05,dk=n-2=65)= 2,000. 3) Influence test: a) Regression equation test, obtained a regression equation Y ̂="28,14"+0,69X Regression determination coefficient test (r2) = 27,1%. Thus Ha is accepted and H0 is rejected.